Sustainability reconsidered: an ethnography of natural dyeing in contemporary Japan - Linton, CA (2021)
Based on twelve months of fieldwork with dyeing craftspeople on the biodiverse island of Amami Ōshima in southern Japan, this thesis explores the complex, often contradictory, intertwining of preservation practices, resource extraction, and access to land that define local relationships with the natural environment. It thereby aims to question widespread discourses about sustainability that assume that small scale ʻtraditionalʼ craft is low impact and therefore more environmentally sustainable. Using apprenticeship methodologies, I reveal that Amamian craft producers are subject to social, economic and bureaucratic pressures, precarities and hierarchies that have equivalences to those widespread in industrial settings. Against a backdrop of uncertainty and instability, my research participants navigate geographically specific practices of ecological care, foraging, cultivating, processing and dyeing and temporally specific experiences of labour migration and lifestyle aspiration. By focusing on their dynamic relationship with local ecologies in order to produce (global) commodities, I was able to study sustaining processes in practice. This in turn forced me to rethink the ideology of sustainability and argue instead for a broader understanding of the extraction, life and value of materials. Value, in this formulation, is not only concentrated on the economic but distributed in ways that benefit the health of a wider conception of community, ecology and sustainability.